Regulation, generic competition and pharmaceutical prices : theory and evidence from a natural experiment - Brekke, Kurt R. (2008)
We study the impact of regulatory regimes on generic competition and pharmaceutical pricing using a unique policy experiment in Norway, where reference pricing (RP) replaced price cap regulation in 2003 for a sub-sample of off-patent products. We exploit a detailed panel dataset at product level covering a wide set of off-patent drugs before and after the policy reform. Off-patent drugs not subject to reference pricing serve as our control group. We find that RP leads to lower relative prices, with the effect being driven by strong brand-name price reductions, and not increases in generic prices. We also find that RP increases generic competition, resulting in lower brand-name market shares. Finally, we show that RP has a strong negative effect on average prices at molecule level, suggesting significant cost-savings.